From Perceived Competence to Measured Performance: The Effect of Scaffolded Project-Based Content Learning on Students’ English Communication Performance in Higher Education - Hesron Ginting (Jurnal Pendidikan: Media, Strategi, dan Metode, 2026)
Project-based English instruction has been widely promoted as an alternative to conventional language teaching because it provides students with opportunities to use English through meaningful, collaborative, and authentic learning tasks. However, previous studies on the integration of content-based instruction and project-based learning have often emphasized students’ self-reported perceptions and single-group pre-test/post-test designs, making it difficult to determine whether the instructional model produces stronger learning outcomes than conventional instruction. Responding to this limitation, this study examined the effect of a scaffolded Project-Based Content Learning model on students’ English communication performance in higher education. The study employed a quasi-experimental pre-test/post-test control group design involving 60 undergraduate students divided into an experimental group and a control group. The experimental group received scaffolded project-based content learning, while the control group received conventional English instruction. Data were collected through English communication performance tests administered before and after the instructional treatment. The data were analyzed using descriptive statistics, paired-sample t-tests, independent-sample t-tests, confidence intervals, and effect size interpretation. The findings showed that both groups improved after instruction, but the experimental group achieved substantially higher improvement than the control group. The experimental group improved from a mean score of 60.33 to 75.27, while the control group improved from 59.93 to 65.07. The difference in gain scores was statistically significant, indicating that scaffolded project-based content learning had a stronger effect on students’ English communication performance. The study concludes that English instruction becomes more effective when students are supported through thematic content, language scaffolding, collaborative project production, peer interaction, and performance-based learning tasks.